2005
DOI: 10.1163/156853805774408577
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Southwest Iberian amphibians to an introduced crayfish, Procambarus clarkii

Abstract: The introduction of predators in amphibian breeding habitats may contribute to the decline or extinction of amphibian populations. Procambarus clarkii, a North American crayfish, was recently introduced in the Iberian Peninsula, being now quite abundant in the southwest, a region with no native crayfish species and where 13 amphibian species may be found. We performed mesocosm experiments to evaluate the vulnerability of amphibian embryos and larvae from those species to P. clarkii. Despite the presence of alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…These systems host a fish community of Cyprinidae and introduced exotic species (Prenda et al, 2006), and the introduced red swamp crayfish (Procam barus clark ii) as the most important large aquatic amphibian predators (e.g. Cruz Rebelo, 2005). Depending on the year and the amount of shadow, the rivers can support dense aquatic vegetation with Ranunculus sp.…”
Section: Study Sitesmentioning
confidence: 99%
“…These systems host a fish community of Cyprinidae and introduced exotic species (Prenda et al, 2006), and the introduced red swamp crayfish (Procam barus clark ii) as the most important large aquatic amphibian predators (e.g. Cruz Rebelo, 2005). Depending on the year and the amount of shadow, the rivers can support dense aquatic vegetation with Ranunculus sp.…”
Section: Study Sitesmentioning
confidence: 99%
“…They are reported to feed on plant and animal detritus, macrophytes and live animals such as molluscs, insects, annelids, nematodes, platyhelminthes, tadpoles and fingerlings ( Fig. 2) (Huner and Barr, 1991;Ilhéu and Bernardo, 1993;Gutiérrez-Yurrita et al, 1998;1999;Parkyn et al, 2001;Correia, 2002;Buck et al, 2003;Cruz and Rebelo, 2005).…”
Section: Trophic Ecologymentioning
confidence: 99%
“…LODGE et al, 1994;NYSTRÖM et al, 2001;GHERARDI and ACQUISTAPACE, 2007). Laboratory experiments have described their predatory efficiency when offered mollusks, amphibians, and fish (GHERARDI et al, 2001;RENAI and GHERARDI, 2004), and field studies have revealed their ability to prey upon both newt eggs (GAMRADT and KATS, 1996) and the embryos and free swimming larvae of up to 13 amphibian species (CRUZ and REBELO, 2005). Surprisingly, little is known about feeding preferences of introduced crayfish species (FEMINELLA and RESH, 1989;BERNARDO, 1993, 1995;CRONIN et al, 2002), notwithstanding that, by feeding selectively, they may exert a strong negative impact on the most consumed resources, thus contributing to biodiversity loss and promoting the homogenization of the invaded community (WARNER and GREEN, 1995;.…”
Section: Introductionmentioning
confidence: 99%